Activity of contezolid against methicillin-resistant Staphylococcus aureus in a rat model of foreign body osteomyelitis - Sebastian C. Herren; Melissa J. Karau; Christina Koscianski; Kerryl E. Greenwood-Quaintance; Jayawant N. Mandrekar; Wen Wang; Robin Patel (Microbiology Spectrum, 2025)
ABSTRACT Contezolid has activity against methicillin-resistant Staphylococcus aureus (MRSA), a common cause of orthopedic infection. In a rat model of foreign body osteomyelitis, 1.3 log10 cfu/g bone and 0.5 log10 cfu/k-wire reduction in MRSA was found in tibiae (P = 0.0186) and K-wires, respectively, of contezolid-treated compared to untreated rats. No MRSA was recovered from animals receiving rifampin alone or in combination with contezolid or vancomycin. There was no emergence of resistance to contezolid, vancomycin, or rifampin.